Development and multi‐institutional validation of an upgrading risk tool for Gleason 6 prostate cancer. Issue 22 (4th September 2013) - Truong, Matthew; Slezak, Jon A.; Lin, Chee Paul; Iremashvili, Viacheslav; Sado, Martins; Razmaria, Aria A.; Leverson, Glen; Soloway, Mark S.; Eggener, Scott E.; Abel, E. Jason; Downs, Tracy M.; Jarrard, David F.
Abstract : BACKGROUND: Many patients with low‐risk prostate cancer (PC) who are diagnosed with Gleason score 6 at biopsy are ultimately found to harbor higher grade PC (Gleason ≥ 7) at radical prostatectomy. This finding increases risk of recurrence and cancer‐specific mortality. Validated clinical tools that are available preoperatively are needed to improve the ability to recognize likelihood of upgrading in patients with low‐risk PC. METHODS: More than 30 clinicopathologic parameters were assessed in consecutive patients with Gleason 6 PC upon biopsy who underwent radical prostatectomy. A nomogram for predicting upgrading (Gleason ≥ 7) on final pathology was generated using multivariable logistic regression in a development cohort of 431 patients. External validation was performed in 2 separate cohorts consisting of 1151 patients and 392 patients. Nomogram performance was assessed using receiver operating characteristic curves, calibration, and decision analysis. RESULTS: On multivariable analysis, variables predicting upgrading were prostate‐specific antigen density using ultrasound (odds ratio [OR] = 229, P  = .003), obesity (OR = 1.90, P  = .05), number of positive cores (OR = 1.23, P  = .01), and maximum core involvement (OR = 0.02, P  = .01). On internal validation, the bootstrap‐corrected predictive accuracy was 0.753. External validation revealed a predictive accuracy of 0.677 and 0.672. The nomogram demonstrated excellent calibration in all 3 cohorts and decision curves demonstrated high net benefit across a wide range of threshold probabilities. The nomogram demonstrated areas under the curve of 0.597 to 0.672 for predicting upgrading in subsets of men with very low‐risk PC who meet active surveillance criteria (all P  < .001), allowing further risk stratification of these individuals. CONCLUSIONS: A nomogram was developed and externally validated that uses preoperative clinical parameters and biopsy findings to predict the risk of pathological upgrading in Gleason 6 patients. This can be used to further inform patients with lower risk PC who are considering treatment or active surveillance. Cancer 2013 ;119:3992–4002. © 2013 American Cancer Society . Abstract : A novel nomogram was developed and externally validated at multiple centers for predicting Gleason score upgrading at radical prostatectomy, for use in patients with Gleason 6 prostate cancer on biopsy. This nomogram may be used in counseling patients regarding their management options.